Professional microsoft® powerpivot for excel® and sharepoint - Harinath, Sivakumar; Pihlgren, Ron; Lee, Denny Guang-Yeu (WILEY, 2010)
With PowerPivot, Microsoft brings the power of Microsoft's business intelligence tools to Excel and SharePoint users. Self-service business intelligence today augments traditional BI methods, allowing faster response time and greater flexibility.